Purification Of The Settling Chamber Of A Pumping Station From Silt Sediments Using A Slurry Pump (Texas Journal of Engineering and Technology, 2024)
This paper discusses one of the operational challenges faced by pumping station forechambers during exploitation: the cleaning of silt deposits from the bottom of the structures. A scheme for a silt cleaning device designed to remove silt deposits from the bottom of the forechamber using a slurry pump is proposed. The device transports the silt mixture through the pumping station's pressure pipeline to an upper reservoir, from where it is then distributed to irrigation fields. A methodology has been developed to determine the key pressure-water consumption parameters and the energy performance indicators of the silt cleaning device. Calculations performed using this methodology indicate that when this device is used to clean silt deposits in the forechamber, the total energy consumption of the pumping station is only 0.051% for cleaning 30 cubic meters of silt.